Potential of natural rubber latex in cement mortar for thermal insulating material in buildings - Awoyera, Paul O.; Althoey, Fadi; Ajinomisan, Hephzibah; Othuman Mydin, Md Azree; Bheel, Naraindas; Sabri Sabri, Mohanad Muayad; Hadidi, Haitham M.; Jayanthi, V.; Ahmad, Mahmood (Frontiers in Materials, 2023)
Mortar is an essential construction material for preventing the absorption of excess moisture and heat by masonry walls. It also serves several other purposes in building decoration and finishing. The improvement of cement mortar's thermal and mechanical properties has been greatly impacted by the addition of polymeric materials. However, polymers added to mortar shouldn't impair either its mechanical or thermal conductivity properties. The main idea of this project is to insulate buildings by reinforcing their constituent mix with natural rubber latex (NRL) to reduce thermal conductance from excessive solar radiation which causes discomfort to building occupants. Consequently, this study presents experimental findings on the influence of natural rubber latex (NRL) on the properties of NRL-modified mortar. Five varying percentages of NRL (0.5%, 1.0%, 1.5%, 2.0% and 2.5%) were added into the mortar. Properties such as thermal conductivity, water absorption capacity, compressive and flexural strengths were evaluated. In addition, scanning electron microscopy was employed for the microstructural investigation. The experimental findings demonstrated that adding 2.5% NRL to mortar increased its thermal conductivity of mortar significantly thus enhancing its insulative properties. Even though adding NRL to mortar decreased the compressive and flexural strengths of some mixes, this wasn't too substantial nor substandard. The tests that were executed demonstrate that the NRL has a huge potential to insulate cement mortar.